PENGARUH STORE ATMOSPHERE DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA WARUNG ASELA KABUPATEN SAMPANG MADURA - Rahmawati, Mega; Tjahjono, Endro; Mulyati, Awin (Universitas 17 Agustus 1945 Surabaya, 2020)
ABSTRACT The development of the business world in Indonesia is increasingly increasing, as evidenced by the increasing number of companies that stand and move in various businesses, including culinary businesses such as the Warung Asela business that is mushrooming every year. Store Atmosphere is one of the determining factors in the price of customer satisfaction. This study tries to explain the effect of store atmosphere and price on consumer satisfaction at Warung Asela Sampang RegencyThis researcher uses a quantitative method with survey research using a questionnaire as an instrument. The population in this study are consumers who have been to Warung Asela Sampang Regency. The sample of this study used a non-probability method (non-random sampling) using a purposive sampling technique totaling 100 respondents. The data analysis technique used is multiple regression analysis.The results of this study indicate that all independent variables namely store atmosphere and price have a positive influence on the dependent variable, namely customer satisfaction. Keywords: store atmosphere, price and customer satisfaction